Respuesta del rendimiento del maíz a fósforo, azufre y zinc en la provincia de Entre Ríos, Argentina - Pautasso, Juan Manuel; Rotondaro, R. (Asociación de Ingenieros Agrónomos del Norte de la Provincia de Buenos Aires, 2022)
The nutrients that mainly condition the yields of extensive crops in Argentina are nitrogen and phosphorus, but the lack of replenishment and continuous agricultural activity have produced a decrease in the availability of other nutrients and could currently become limiting. These include zinc and sulfur. The use of fertilizers with only P and N at the sowing of the maize crop has been a traditional practice in the province of Entre Ríos. Currently other sources have valuesclose to their concentration in terms of these nutrients (P and N) and have S and Zn in their composition. With the objective of evaluating the effect of the application of P, S and Zn versus only P, 10 trials were carried out in producers' fields during three campaigns in different localities of the province of Entre Ríos, Argentina. In a joint analysis it was observed that the addition of P produced an increase in corn yield by 13% and a more complete fertilization (PSZn) by 21%, both treatments were statistically different from the control (p<0.05). When carrying out a contrast study between the traditional fertilization treatment (only with P) versus a more complete fertilization (PSZn) it yielded a p-value of 0.06, which leads us to conclude that there is a strong tendency to increase yield of corn with this fertilization.